Assembly strategies for rubber-degrading microbial consortia based on omics tools - Cui, Chengda; Jiang, Mengke; Zhang, Chengxiao; Zhang, Naxue; Jin, Feng-Jie; Li, Taihua; Lee, Hyung-Gwan; Jin, Long (Frontiers in Bioengineering and Biotechnology, 2023)
Numerous microorganisms, including bacteria and fungus, have been identified as capable of degrading rubber. Rubber biodegradation is still understudied due to its high stability and the lack of well-defined pathways and efficient enzymes involved in microorganism metabolism. However, rubber products manufacture and usage cause substantial environmental issues, and present physical-chemical methods involve dangerous chemical solvents, massive energy, and trash with health hazards. Eco-friendly solutions are required in this context, and biotechnological rubber treatment offers considerable promise. The structural and functional enzymes involved in poly (cis-1,4-isoprene) rubber and their cleavage mechanisms have been extensively studied. Similarly, novel bacterial strains capable of degrading polymers have been investigated. In contrast, relatively few studies have been conducted to establish natural rubber (NR) degrading bacterial consortia based on metagenomics, considering process optimization, cost effective approaches and larger scale experiments seeking practical and realistic applications. In light of the obstacles encountered during the constructing NR-degrading consortia, this study proposes the utilization of multi-omics tools to discern the underlying mechanisms and metabolites of rubber degradation, as well as associated enzymes and effective synthesized microbial consortia. In addition, the utilization of omics tool-based methods is suggested as a primary research direction for the development of synthesized microbial consortia in the future.